Perlindungan Hukum Produk Terdaftar Berdasarkan Indikasi Geografis - Zuhriati khalid; Sugih Ayu Pratitis (Universitas Quality, 2022)
Protection against Geographical Indications is a new thing in the Intellectual Property Rights protection system. In the protection system against Geographical Indications, it is regulated in how to determine the ownership of a product based on Geographical Indications, what form of legal protection is for products registered with Geographical Indications, and the role of the government in improving Geographical Indications products in Indonesia explaining where Geographical Indications are. The method used in writing this research is to use a normative juridical approach. The type of data used is primary data, secondary data. While the data collection method is done through library research (Library Research). The result of the research is that the protection of Geographical Index is a new thing in the Intellectual Property Rights protection system. The system is regulated in the TRIP's agreement which requires countries to develop legal protection against fraudulent competition practices or acts. Indications that indicate that an item originates from the area as the origin of the item, reputation or other special character of the item can be largely determined by the Essential factor by the Geographical factor of the item concerned.The government's role in improving Geographical Indication products in Indonesia is through the government's efforts to increase the utilization of Geographical Indication products in Indonesia, namely by maximizing the use of Geographical Indications where in this case the government is represented by the Ministry of Industry and Trade (Depperindag), namely by providing guidance or by conducting tracing and collection by identifying geographical indication products in collaboration with relevant national and international cross-departments.